Субмаринная разгрузка подземных вод на мысе Айя (Крым) - Иванов, В.А.; Прусов, А.В.; Чепыженко, А.И. (Доповіді НАН України, 2010)
Наведено результати натурних спостережень субмаринного розвантаження пiдземних вод у м. Айя (Крим) наприкiнцi гiдрологiчного лiта 2008 р. Вимiряно швидкостi течiї, температуру, солонiсть i мутнiсть в однiй з карстових порожнин, а також на полiгонi поблизу неї. Оцiнки дебiту субмаринного розвантаження порiвнюються з аналогiчними оцiнками, отриманими ранiше. The paper reports the data of on-location observations of a submarine ground water discharge collected in summer 2008 in the region of the cape Aya (Crimea, Ukraine). In particular, we present the data on the current speed, temperature, salinity, and turbidity collected in a grotto and the area around it. The submarine ground water discharge is evaluated, and the results are compared with those obtained in the previous studies.